Associations of plasma metal concentrations with the risks of all-cause and cardiovascular disease mortality in Chinese adults. (December 2021) - Shi, Limei; Yuan, Yu; Xiao, Yang; Long, Pinpin; Li, Wending; Yu, Yanqiu; Liu, Yiyi; Liu, Kang; Wang, Hao; Zhou, Lue; Yang, Handong; Li, Xiulou; et al.
Highlights: Metals are crucial determinants and predictors of premature death in Chinese adults. Selenium and thallium may reduce the risks of all-cause and CVD mortality. Molybdenum and vanadium would confer risks for all-cause and CVD mortality. Plasma metal score provides in-depth characterization of multiple metal exposures. Plasma metal score would improve the predictive ability for further mortality risk. Abstract: Background: Exposure to metals/metalloids from both the natural environment and anthropogenic sources have a complex influence on human health. However, relatively few studies have explored the relations of exposure to multiple metals/metalloids with mortality. Therefore, this prospective study aims to examine the relations of multiple metal/metalloids exposures with all-cause and cardiovascular disease (CVD) mortality. Methods: A total of 6155 participants within the Dongfeng-Tongji (DF-TJ) cohort were involved in this analysis, which were followed for mortality until December 31, 2018. We applied inductively coupled plasma mass spectrometry (ICP-MS) to measure baseline plasma concentrations of 23 metals. We utilized Cox regression models to calculate the hazard ratios (HRs) for all-cause and CVD mortality associated with metal concentrations. We proposed plasma metal score to assess the simultaneous exposure to multiple metals through summing each metal concentration weighted by the regression coefficients with all-cause mortality. Results: During the follow-up (mean duration, 9.8 years), we ascertained 876 deaths, including 416 deaths of CVD (157 deaths of coronary heart disease and 259 deaths of stroke). In the multiple-metals model, after adjusting for potential confounders, plasma copper, molybdenum, and vanadium were positively associated with all-cause mortality, whereas manganese, selenium, and thallium were negatively associated with the risk of all-cause mortality, with adjusted HRs (95% Confidence Interval, CI) of the fourth quartiles were 1.73 (1.42–2.11, P-trend < 0.001) for copper, 1.33 (1.09–1.63, P-trend = 0.005) for molybdenum, 1.43 (1.16–1.77, P-trend < 0.001) for vanadium, 0.74 (0.58–0.94, P-trend = 0.005) for manganese, 0.68 (0.56–0.83, P-trend < 0.001) for selenium, and 0.74 (0.59–0.92, P-trend = 0.002) for thallium, respectively. Positive associations were observed between plasma copper, molybdenum, vanadium concentrations and CVD mortality, whereas negative associations were found for plasma selenium and thallium concentrations with CVD mortality in the multiple-metals model. Compared with the first quartiles, the HRs of fourth quartiles were 1.94 (1.45–2.58, P-trend < 0.001) for copper, 1.72 (1.26–2.35, P-trend < 0.001) for molybdenum, 1.81 (1.32–2.47, P-trend < 0.001) for vanadium, 0.67 (0.50–0.89, P-trend = 0.003) for selenium, and 0.58 (0.41–0.81, P-trend < 0.001) for thallium, respectively. The plasma metal score was significantly associated with higher risks of all-cause and CVD death in dose–response fashions. When compared with the first quartiles of plasma metal score, the HRs of fourth quartiles were 2.16 (1.76–2.64; P-trend < 0.001) for all-cause mortality and 3.00 (2.24–4.02; P-trend < 0.001) for CVD mortality. Conclusions: The study indicated that several plasma metals/metalloids were key determinants and predictors of all-cause and CVD death in the Chinese population. Our findings highlighted the importance to comprehensively assess and monitor multiple metals/metalloids exposures.